Morphological and physiological response of some Iranian ecotypes of Leonurus cardiaca L. to drought stress - Fatemeh Borna (University of Birjand, 2021)
Purpose: Motherwort (Leonurus cardiaca), a medicinal plant of the Lamiaceae family, has a great diversity and wide distribution in Iran. It is essential due to having leonurine with blood dilution and muscle relaxation effects. Research method: To evaluate the response of the Iranian Motherwort ecotypes in drought environments, an experiment was carried out in split plot design based on RCBD with three replications. Three irrigation levels were considered as main plots, including %100, one-third, and two-third of field capacity, and four ecotypes as sub-plots including Kerman, Taleghan, Sarab and Khansar. The experiment was conducted at Horticultural Research Station, the University of Tehran, in Karaj. Findings: The results showed that water stress affected morphological traits significantly. Water stress had a significant increasing effect on the phenolic and flavonoid contents and antioxidant activity of Motherwort ecotypes. The highest and the lowest total phenol content were observed in Taleghan and Kerman ecotypes, 7.34 and 4.21 mg/mg fresh weight, respectively. The amount and the percentage of leonurine were increased by water stress. The highest and the lowest values of leonurine were observed in the ecotypes of Taleghan and Sarab, respectively, in all three levels of irrigation. There were significant correlations between dry weight (-0.43), antioxidant (0.36), proline (-0.35), catalase (0.4), and the percentage of leonurine. Research limitations: There were no limitations to the report. Originality/Value: It was found a significant variation among the ecotypes in response to water stress. The ecotypes of Taleghan and Sarab were the most tolerant and the most susceptible ecotypes to drought stress among the studied ecotypes.